2015
DOI: 10.5194/bg-12-3913-2015
|View full text |Cite
|
Sign up to set email alerts
|

Coupling δ<sup>2</sup>H and δ<sup>18</sup>O biomarker results yields information on relative humidity and isotopic composition of precipitation – a climate transect validation study

Abstract: Abstract. The hydrogen isotopic composition (δ2H) of leaf waxes, especially of n-alkanes (δ2Hn-alkanes), is increasingly used for paleohydrological and paleoclimate reconstructions. However, it is challenging to disentangle past changes in the isotopic composition of precipitation and changes in evapotranspirative enrichment of leaf water, which are both recorded in leaf wax δ2H values. In order to overcome this limitation, Zech M. et al. (2013) proposed a coupled δ2Hn-alkanes–δ18Osugar biomarker approach. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 80 publications
3
41
0
Order By: Relevance
“…Finally, our findings have important implications for ecophysiological and hydrological sciences using oxygen (and potentially also hydrogen) isotopes of various plant biomarkers such as cellulose, hemicellulose and n‐alkanes to decipher temporally and spatially integrated information about past environmental conditions and associated plant functional responses (Hepp et al ., ; Tuthorn et al ., ). This is especially important for organic molecules derived from plants, sediments, or soils in regions and seasons that experience high humidity conditions (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, our findings have important implications for ecophysiological and hydrological sciences using oxygen (and potentially also hydrogen) isotopes of various plant biomarkers such as cellulose, hemicellulose and n‐alkanes to decipher temporally and spatially integrated information about past environmental conditions and associated plant functional responses (Hepp et al ., ; Tuthorn et al ., ). This is especially important for organic molecules derived from plants, sediments, or soils in regions and seasons that experience high humidity conditions (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Also climatically driven changes of deuterium content in local precipitation as well as changes of temperature with altitude need to be taken into account. A way out of this dilemma could be a coupled δ 2 H-δ 18 O approach in terrestrial and lacustrine paleoclimate studies as suggested by Zech et al [67], Hepp et al [82] and Tuthorn et al [83].…”
Section: Discussionmentioning
confidence: 98%
“…However, individual plants show considerable δ 13 C wax and δD wax variability even within species or plant functional type, and thus, plant δ 13 C wax and δD wax distributions contain significant variability uncorrelated with environmental parameters (e.g., Sachse et al, 2012). The n-alkanes are durable molecules; they withstand weathering and to some extent bacterial degradation (e.g., Chikaraishi & Naraoka, 2006;Nguyen Tu et al, 2011;Pond et al, 2002;Tuthorn et al, 2015;Zech et al, 2011), and are incorporated into the sedimentary cycle and accumulate in soils and lakes (e.g., Lichtfouse et al, 1998;Pedentchouk et al, 2006). Throughout this process, leaf waxes are integrated over space and time, and soil δ 13 C wax and δD wax variability is reduced.…”
Section: Introductionmentioning
confidence: 99%